Atmospheric plasma-catalytic treatment of methyl orange - Addou, Ahmed; Benstaali, B; Haji, S; Al-Bastaki, N; Brisset, JL (19th International Symposium on Plasma Chemistry, Bochum, Germany, 2009)
Atmospheric gliding arc discharges in humid air are used for the treatment of M e- thyl Orange (MO) solutions for depollution purposes. Highly reactive neutral hydroxyl rad i- cals OH  and NO  are produced in the plasma. Their interaction with the solution is invest i- gated using UV/Visible spectroscopy . The plasma treatment shows the creation of interm e- diate species syst ematically followed by their degradation leading to one end product. The presence of hydrogen peroxide (H 2 O 2 ) and titanium oxide (TiO 2 ) as catalyst s differently i n- fluences the plasma treatment of the MO solution. H 2 O 2 influences further the direct chemical reactions due its straightforward decomposition under UV radiations while TiO 2 has to be a c- tivated before releas ing species that contribut e to the highly oxidant HO  radicals production .
Keywords: Gliding discharge; humid air, non thermal plasma; at mospheric pressure; Pla s- ma -chemical degradation, Methyl Orange; Hydrogen peroxide.